Testing the reliability of global surface temperature reconstructions of the Last Glacial Cycle with pseudo-proxy experiments - J.-P. Baudouin; N. Weitzel; M. May; L. Jonkers; A. M. Dolman; K. Rehfeld; K. Rehfeld (Climate of the Past, 2025)
Reconstructions of past variations in the global mean surface temperature (GMST) are used to characterise the Earth system response to perturbations and to validate Earth system simulations. Beyond the instrumental period, reconstructions rely on local proxy temperature records and algorithms aggregating these records. Here, we propose to establish standards for evaluating the performance of such reconstruction algorithms. Our framework relies on pseudo-proxy experiments (PPEs). That is, we test the ability of an algorithm to reconstruct a simulated GMST, using artificially generated proxy data created from the same simulation. We apply the framework to an adapted version of the GMST reconstruction algorithm used in Snyder (2016) and the metadata of the synthesis of marine proxy records for the temperature of the last 130 kyr from Jonkers et al. (2020). We use an ensemble of four transient simulations of the Last Glacial Cycle (LGC) or the last 25 kyr for the pseudo-proxy experiments.